A new model of urban regeneration and economic revitalisation: the I.D.E.A. District, San Diego - Parisi, Luana; Biancuzzo, Laura (Journal of Architecture and Urbanism, 2021)
In the 21st century globalized economy, innovation is a crucial factor within strategies targeted at growing and sustaining competitiveness of regions and cities. The emerging trend of innovation-led urban planning initiatives provides strong evidence of how cities are implementing strategies to promote innovation mainstreaming. Hence, these innovationoriented policies are currently translated into the creation of innovation districts, becoming part of the urban settlement dynamics towards regeneration processes. This paper intends to explore the new paradigm of urban development initiatives driven by the increasing demand of innovation. Accordingly, innovation districts will be investigated by identifying the role, as well as the influence, of the different actors who nurture and accelerate the innovation process at urban level. The I.D.E.A. District case study will be examined, by pointing out the policies and planning initiatives undertaken in Downtown San Diego. Findings from this research will evaluate the effectiveness of the new generation of urban planning initiatives in supporting urban growth strategies. Additionally, the level of public private partnership effectiveness in supporting the development of innovation districts will be highlighted. Useful lessons can be drawn in encouraging planners and policymakers towards implementing these new innovation-oriented urban regeneration initiatives within urban growth strategies, important for enhancing competitiveness and for improving liveability by providing solutions for a more efficient land use.